2007
DOI: 10.1107/s0021889807040010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the presence of U–Mo–Al ternary compounds in the U–Mo/Al interaction layer grown by thermal annealing: a coupled micro X-ray diffraction and micro X-ray absorption spectroscopy study

Abstract: The systematic presence of the ternary phases U6Mo4Al43 and UMo2Al20 is reported in a U–Mo/Al interaction layer grown by thermal annealing. This work shows, therefore, the low Mo solubility in UAl3 and UAl4 binary phases; it contradicts the hypothesis of the formation of (U,Mo)Al3 and (U,Mo)Al4 solid solutions often admitted in the literature. Using µ‐XAS (micro X‐ray absorption spectroscopy) at the Mo K edge and µ‐XRD (micro X‐ray diffraction), the heterogeneity of the interaction layer obtained on a γ‐U0.85M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 18 publications
(21 reference statements)
1
47
1
1
Order By: Relevance
“…Perez et al [23] annealed a series of diffusion couples of U-Mo vs pure Al (99.999 pct) at 823 K (550°C), and determined the (U,Mo)Al 4 as the average composition of the interdiffusion zone based on electron probe microanalysis (EPMA). Mirandou et al, [24] Palancher et al, [25] and Mazaudier et al [26] observed, in addition to the (U,Mo)Al 3 and (U,Mo)Al 4 phases, the U 6 Mo 4 Al 43 and UMo 2 Al 20 ternary intermetallic phases, along with the cfi(a+d) decomposition of the U-Mo alloy. More recently, Mirandou et al [27] examined diffusion couples of U-7 wt pct Mo vs AA6061 for 823 K (550°C) for 3 hours and 613 K (340°C) for 3216 hours.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Perez et al [23] annealed a series of diffusion couples of U-Mo vs pure Al (99.999 pct) at 823 K (550°C), and determined the (U,Mo)Al 4 as the average composition of the interdiffusion zone based on electron probe microanalysis (EPMA). Mirandou et al, [24] Palancher et al, [25] and Mazaudier et al [26] observed, in addition to the (U,Mo)Al 3 and (U,Mo)Al 4 phases, the U 6 Mo 4 Al 43 and UMo 2 Al 20 ternary intermetallic phases, along with the cfi(a+d) decomposition of the U-Mo alloy. More recently, Mirandou et al [27] examined diffusion couples of U-7 wt pct Mo vs AA6061 for 823 K (550°C) for 3 hours and 613 K (340°C) for 3216 hours.…”
mentioning
confidence: 95%
“…Keiser et al, [22] Palancher et al, [25] and Perez et al [23,28] reported concentration profiles of sufficient thickness to permit analysis, by energy dispersive spectroscopy (EDS) and EPMA, of the interaction layer. Concentration profiles of U, Mo, and Al show negligible gradients with near constant concentrations, particularly for Al throughout the interdiffusion zone thickness.…”
mentioning
confidence: 98%
“…The reaction products are undesirable because they generate a low conductivity interaction layer (IL) by nuclear fission, leading to potential structural failure 3,8,9 . The thermal experiments are normally carried out below γ-phase temperature formation to simulate the interdiffusion and phases formation in U-Mo-Al 10 . The more common observed phases have been (U,Mo)Al 2 , (U,Mo)Al 3 (U,Mo)AL 4 [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Palancher identified UAl 2 , UAl 3 , and U 6 Mo 4 Al 43 in ILs formed during anneal at 600°C. 24 In a separate publication, Palancher 25 identified the presence of (U,Mo)Al 3 , (U,Mo)Al 4 , UMo 2 Al 20 , and U 6 Mo 4 Al 43 in a diffusion couple and a dispersion fuel annealed at 600 and 500°C, respectively. These results are somewhat contradictory, although the results based on the dispersion fuels are based on tests run at different temperatures.…”
Section: Phase Identificationmentioning
confidence: 99%